Assessment of Bacterial Contamination in Locally Sourced Chicken Meat from Markets Kendari City, Indonesia - Risawa1, Risma Wilasakti; Has, Hamdan; Yaddi, Yamin; Sahaba, La Ode; Dewi, Fitria; Astarika, Rina; Daud, Denvy Meidian; Zulkarnain, Deki (Pascasarjana Universitas Halu Oleo, 2024)
ABSTRACT This research aims to ensure the safety of livestock-origin food products through the evaluation of microbial contamination potential in production-support facilities. The study was conducted by isolating and characterizing bacteria from poultry slaughter facilities in several traditional markets in Kendari City. Swab samples were taken from chicken holding pens in five traditional markets. The market locations were determined using purposive sampling, with the daily slaughter quantity as the main indicator. Isolation was performed by observing bacterial colony growth, and characterization was carried out by observing the morphology of bacterial colonies on specific differential media using Eosin Methylene Blue Agar (EMBA). Bacterial confirmation was done through microscopic observation based on the shape and morphology of bacteria in Gram staining. The results of this study indicate that bacteria can be isolated from all poultry slaughterhouses in traditional markets in Kendari City. Characterization results show that the bacteria were confirmed as Escherichia coli, Salmonella sp., and Pseudomonas sp. The low implementation of Good Hygiene Practices in production execution is a major supporting factor for the presence of bacteria as a source of contamination. Periodic supervision by relevant authorities is necessary as an effort to ensure the safety of livestock-origin food products.